The Relationship between HR Quality and Unemployment and Its Effect on Poverty Levels in North Sumatra 2005-2020 - Napitupulu, Venesia; Hasugian, Lola Alvita; Ananda, Wizya Vita; Safitri, Maulinda; Rinaldi, Muammar; Adek Apriyandi (Outline Publisher, 2024)
This research discusses the relationship between HR quality and unemployment and its influence on poverty levels in North Sumatra 2005-2020. This research was conducted using secondary data and then managed using multiple linear regression tests and classic assumption tests (including normality tests, autocorrelation tests, heteroscedasticity tests, and multicollinearity tests). This research was obtained from the 2005-2020 time series data. The results obtained from the results of this study showed that unemployment has a positive and significant effect on the poverty rate in North Sumatra